Perancangan Enterprise Architecture Menggunakan The Open Group Architecture Framework Architecture Development Method - Hendri Irawan; Nurul Mutiah; Ferdy Febriyanto (Maranatha University Press, 2023)
As one of the institutions that often deal directly with the interests of the community, the village government requires good information technology management to support the work of village government. The village government whose mission is to improve village governance in the field of information technology is Sungai Rengas Village, Sungai Kakap Sub-District, Kubu Raya Regency, so research on enterprise architecture design was carried out in the Sungai Rengas Village Government. The goal of this study is to design an enterprise architecture that is suitable for village government systems and can be the first step in forming an electronic-based village government system. This study uses the TOGAF ADM 9.2 framework which provides a detailed method for designing enterprise architecture. The design is carried out starting from the preliminary phase to the migration planning phase, each stage will be designed with the enterprise baseline and target architecture and then gap analysis will be carried out. The results of this study are the design of enterprise architecture starting from business architecture, data architecture, application architecture, and technology architecture.Tests were carried out on the results of the enterprise architecture design using the enterprise architecture scorecard. The test results stated that the enterprise architecture designed for the government of Sungai Rengas Village was valid or the design was in conformance with the baseline conditions and targets for the government of Sungai Rengas Village because the results of the percentage of testing had surpassed 50%, that is 82.95%.